Knowledge, attitude and practice of self-medication among undergraduate diploma nursing students in School of Health Sciences, Universiti Sains Malaysia (USM) - Zainuddin, Muyassarah (2020)
The introductory of self-medication is no foreign to our society as its advertising factors has been long poses either through peers, or exposure of knowledge and mass media. Lots of study has been conducted in determining the students’ knowledge, attitude, and practice in correlation to self-medication. The objective of this study is to determine the knowledge, attitude, and practice of self-medication among undergraduate Diploma nursing students in School of Health Sciences, Universiti Sains Malaysia (USM). A cross-sectional study via convenient sampling was applied in this study to describe the knowledge, attitude, and practice of self-medication among undergraduate Diploma nursing students in School of Health Sciences, Universiti Sains Malaysia (USM). Data were collected by using a structured self-administered questionnaire and analysed via Statistical Package for Social Science (SPSS) version 22.0. Pearson’s Chi-square test was used to analyse the fourth objective, which was to determine the association between selected data (gender and academic year) with the level of knowledge and attitude on self-medication among undergraduate Diploma nursing students with significant level ( value) was set <0.05. A total of 118 undergraduate Diploma nursing students in School of Health Sciences, Universiti Sains Malaysia (USM) were recruited. The results of association between selected socio-demographic characteristics (gender and academic year) and the level of knowledge on self-medication had reported not significant associated (p-value > 0.05) for gender while a positive correlation between academic year and self-medication (p-value <0.05). The association between selected socio-demographic characteristic (gender) and the level of attitude on self-medication among undergraduate Diploma nursing had found not significant associated (p-value= 0.282). Between socio-demographic characteristic (academic year) and the attitude level on self-medication, it suggested not significant relation as the p-value is more than 0.05 (p-value= 0.763). This study gave out basis information that might be useful as a reference especially in designing more conventional and new ideas for educational activities among nursing students in educational institution.